Effects of orbicularis oculi flap anchorage to the periosteum of the upper orbital rim on the lower eyelid position after transcutaneous blepharoplasty: Statistical analysis of clinical outcomes. Issue 3 (March 2017) - Innocenti, Alessandro; Mori, Francesco; Melita, Dario; Dreassi, Emanuela; Innocenti, Marco
Summary: Background: The aging process affects the skin, muscle, and fat of the eyes in a different manner. Their individual rejuvenation would require specific surgical treatments according to their particular demands. In the present study, we analyzed the effect of an orbicularis oculi muscle flap fixed to the superior orbital rim to prevent lower eyelid dislocation during transcutaneous blepharoplasty. Methods: The study was conducted retrospectively comparing pre- and postoperative images of two different groups of patients: group A (20 patients) treated with an orbicularis oculi flap and group B (17 patients) treated without the flap. Pre- and postoperative distances between the center of the pupil and upper border of the lower lid at the midpupillary line were measured in each photo and then compared and statistically analyzed. Results: The mean age of the 37 patients was 57 years. From the estimated linear mixed model, we observed a significant effect of the presence of the flap (p-value < 0.0001). All the patients treated with the orbicularis oculi flap (group A) showed a cranial movement of the lower eyelid, although only minimally. All the patients treated without the muscle flap (Group B) showed a caudal movement of the lower eyelid. In total, 47% of the eyes in group B showed a positive variation of >10%. Conclusion: The study suggests that the anchorage of the orbicularis muscle flap to the upper orbital rim reinforces the lower eyelid's anterior lamellae. It efficiently stabilizes lower eyelid position after transcutaneous blepharoplasty, thus confirming clinical results and improving surgical outcomes even in patients with minimal or no eyelid laxity.